Influence of low-level laser therapy on inflammation, collagen fiber maturation, and tertiary dentin deposition in the pulp of bleached teeth - Terayama, Amanda Miyuki [UNESP]; Benetti, Francine [UNESP]; de Araújo Lopes, Juliana Maria [UNESP]; Barbosa, Jéssica Galbiati [UNESP]; Silva, Isabela Joane Prado [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Briso, André Luiz Fraga [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Springer Nature, 2020)
Objectives: We evaluated the effects of low-level laser therapy (LLLT) using an infrared laser (IRL) and a red laser (RL) on the pulp of molar teeth in rats after dental bleaching to assess inflammation, collagen fiber maturation, and tertiary dentin formation. Materials and methods: Eighty Wistar rats (Rattus norvegicus, albinus) were randomly divided into eight groups with 10 hemimaxillae in each of the following: control; bleached (Ble, 35% hydrogen peroxide [H2O2]); Ble-1IRL and Ble-1RL (one IRL [808 nm, 30 s, 3 J] or RL [660 nm, 15 s, 1.5 J] application immediately after H2O2); Ble-3IRL and Ble-3RL (three [immediately, 24 h, and 48 h] IRL or RL applications after H2O2); and 3IRL and 3RL (three IRL or RL applications without bleaching). The rats were euthanized after 2 and 30 days for histological evaluation of inflammation (hematoxylin-eosin) and maturation of collagen fibers (picrosirius red). Additionally, the dentin deposition in the specimens obtained at 30 days was quantified via microtomography of the pulp chamber volume. Statistical analyses were performed (P < 0.05). Results: Initially, severe damages to the pulp were observed in the Ble and Ble-1RL groups. Ble-1IRL and Ble-3RL groups showed lower inflammation. The bleached groups had a greater amount of mature collagen fibers than the control group. The Ble-3IRL group had a greater number of immature fibers than the Ble group. At 30 days, there was an absence of inflammation and equal proportion of mature and immature collagen fibers. All bleached groups showed a reduction in the volume of the pulp chamber. Conclusion: Three consecutive applications of RL and one IRL application can minimize damage to the pulp of bleached teeth, whereas three IRL applications can minimize pulp fibrosis. However, LLLT did not prevent deposition of tertiary dentin. Clinical relevance: This study describes LLLT protocols capable of minimizing inflammation and maturation of collagen fibers in pulp tissue after dental bleaching. However, the protocols proved insufficient for reducing the formation of tertiary dentin in bleached teeth.
Keywords: Dental bleaching; Dental pulp; Hydrogen peroxide; Low-level laser therapy; Tertiary dentin